Improving Outcomes with Sequential Fixation Using Long-Threaded Screws for Valgus-Impacted Femoral Neck Fractures - Jeong-Hyun Koh; Seungyeob Sakong; Won-Tae Cho; Sumin Lim; Hyung Keun Song (Medicina)
Background and Objectives: Valgus-impacted femoral neck fractures (OTA 31B1.1 and 31B1.2) are considered stable fractures with favorable outcomes compared to displaced fractures. However, complications such as femoral neck shortening, screw sliding, and suboptimal recovery can occur, particularly in severe deformities. This study evaluated the outcomes of a sequential fixation technique using short-threaded screws followed by long-threaded screws. Materials and Methods: This prospective study included 135 patients aged 60 years or older with valgus-impacted femoral neck fractures (OTA 31B1.1 and 31B1.2) treated between March 2017 and February 2021. Patients were divided into two groups: those treated solely with short-threaded screws (the control group) and those treated using a sequential fixation technique involving initial compression with short-threaded screws followed by stabilization with long-threaded screws. Exclusion criteria included follow-up < 12 months, pathological fractures, high-energy trauma, or periprosthetic fractures. Clinical outcomes, including the Harris Hip Score (HHS), and radiological parameters, such as screw sliding distance (SDS) and fixation failure, were analyzed. Multivariate regression identified predictors of outcomes to assess the effectiveness of the sequential fixation technique. Results: The mean follow-up was 38.3 months. Multivariate regression revealed that posterior tilt > 15° (β = 2.944, p < 0.001) and the use of long-threaded screws (β = −1.906, p < 0.001) were significant predictors of reduced SDS. Posterior tilt > 15° (OR 15.085, p = 0.002), valgus tilt > 15° (OR 28.616, p = 0.002), and bone mineral density (OR 0.285, p = 0.005) were predictors of fixation failure, while long-threaded screws significantly reduced fixation failure risk (OR 0.062, p = 0.005). Conclusions: The sequential use of short-threaded screws for compression, followed by long-threaded screws for stabilization, effectively reduced screw sliding and fixation failure while improving functional and radiological outcomes. This technique shows promise as an effective treatment for valgus-impacted femoral neck fractures.